Concept of Multiculturalism in Modern Azerbaijan Politics - D. S. Zheriborov (Научный диалог)
The concept of multiculturalism of Azerbaijan is considered, which plays a significant role in today’s domestic and foreign policy of Azerbaijan. The relevance of the study is determined, in particular, by the fact that 2016 was declared in Azerbaijan “the year of multiculturalism.” It is reported that during this year there were a huge number of events dedicated to multiculturalism - from the global forum of the UN Alliance of civilizations to youth summer and winter schools. The article examines the origin and content of modern Azerbaijan’s policy of multiculturalism. Variability of its interpretations is shown, even at the domestic level. It is proved that the Azerbaijani multiculturalism typologically can be assigned to the traditional model of multiculturalism, characteristic for many countries of the world where there are diverse religions, ethnic groups and culture, such as in Russia. It is shown that Azerbaijan is actively using the policy of multiculturalism to promote a positive image of the country globally with the participation of international organizations and in bilateral relations with individual countries.